A Study of Clinicohistopathological Correlation in Patients of Hansen Disease - Pradhan, Manish; Rai, Anjan; Karki, Sunita; KC, Srijana (Nepal Journal of Dermatology, Venereology & Leprology, 2026)
Background: Hansen's disease (Leprosy), caused by Mycobacterium leprae, is a chronic granulomatous condition with varied clinical presentations reflecting the host's immune response. Clinical and histological classifications may differ, leading to diagnostic errors. Histopathology offers definitive information on granulomas, bacillary load, and tissue changes. Thus, clinico-histopathological correlation is crucial for accurate diagnosis and appropriate treatment. Objectives: To study the clinic-histopathological comparison in patients with Hansen's disease and evaluate the concordance between clinical and histopathological findings. Materials and Methods: This retrospective observational study analyzed records of patients with Hansen’s disease who underwent skin biopsy at a tertiary care center in Nepal during a two-year study period. Cases with complete clinical and histopathological data were included. Clinical and histopathological classifications were performed according to the Ridley-Jopling spectrum. H&E staining and Fite-Faraco stain for bacilli was done. Clinico-histopathological correlation was assessed by comparing clinical and histopathological diagnoses. Data were analyzed using SPSS, with categorical variables expressed as frequencies, percentages and means. Clinicopathological correlation between clinical and histopathological classification of leprosy was assessed using Cohen’s kappa statistic. Results: A total of 150 patients aged 11-85 years were included, with a mean age of 43.75 ± 15.89 years and male predominance. Clinically, lepromatous leprosy was most common, while histopathology most often showed tuberculoid leprosy. The overall agreement was moderate (κ = 0.48) and was statistically significant (p < 0.001). The observed agreement between the two methods was 57.3%.The agreement of tuberculoid leprosy was 76.66% and lepromatous leprosy 75.75%, while it was moderate in borderline tuberculoid (54.83%); and low in borderline (30%) and borderline lepromatous (33.33%). Substantial reclassification occurred particularly within the borderline spectrum, with BB being clinically overestimated and IL being underestimated. Conclusion: A combined clinic-histopathological approach is essential for accurate classification, especially in borderline cases. While clinical features provide an initial impression, histopathology remains the gold standard for confirmation. A combined approach enhances diagnostic precision, ensures appropriate therapy, and contributes to better patient outcomes.